2021
DOI: 10.1021/acsabm.1c00458
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrid-Reinforced Gelatin-Ureidopyrimidinone-Based Self-healing Injectable Hydrogels for Tissue Engineering Applications

Abstract: The traditional hydrogels are prone to break due to the applied stress. The deformation of the implanted hydrogels would result in the loss of structural integrity, leading to the failure of hydrogel functionalities and tissue regeneration. Selfhealing hydrogels (AG-UPy), composed of oxidized alginate and ureidopyrimidinonefunctionalized gelatin (G-UPy), were developed to address this challenge. These selfhealing hydrogels possess two independent healing mechanisms, viz., Schiff base formation and UPy dimeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…The addition of nanoclay resulted in a steadier release of the growth factor [16]. These results were in accordance with other studies that demonstrated the great ability of nanoclays to absorb proteins as well as to form tighter hydrogels [49][50][51].…”
Section: Bioprintingsupporting
confidence: 92%
See 1 more Smart Citation
“…The addition of nanoclay resulted in a steadier release of the growth factor [16]. These results were in accordance with other studies that demonstrated the great ability of nanoclays to absorb proteins as well as to form tighter hydrogels [49][50][51].…”
Section: Bioprintingsupporting
confidence: 92%
“…Nanoclays are silicate-derived multilayers that have been shown to play a key role in the physiology of a wide range of tissues such as bone [48]. Several studies have proved that these nanoparticles are able to complement the already adequate properties of gelatin hydrogels for bone tissue regeneration [16,[49][50][51]. One of the main advantages of nanoclays consists in improving the gelatin's poor mechanical properties.…”
Section: Bioprintingmentioning
confidence: 99%
“…Self‐healing is defined as the ability of a material to recover or repair the damage 13–16 . It can be classified as the intrinsic and the extrinsic.…”
Section: Introductionmentioning
confidence: 99%
“…12 Self-healing is defined as the ability of a material to recover or repair the damage. [13][14][15][16] It can be classified as the intrinsic and the extrinsic. In extrinsic self-healing materials, healing agents are dispersed in the matrix and released after being damaged.…”
mentioning
confidence: 99%
“…They are ideal candidates for immobilizing enzymes, nucleic acids, proteins or peptides because of their porous structure and soft nature, which can mimic physiological environments and increase the loading capacity [8]. Their applications are found in controlled release, drug delivery, immunomodulation, tissue engineering, or sensing and biosensing [9][10][11][12][13] and the hydrogel-based materials market is forecasted to reach US $31.4 billion by 2027 (https:// www. allie dmark etres earch.…”
Section: Introductionmentioning
confidence: 99%